Modification method for improving corrosion resistance of chromizing coating
By adding rare earth oxide La2O3 and modified element Hf to the permeating agent component of the chromium coating and carrying out vacuum embedding and permeating treatment, the problem of poor stability of the chromium coating in high-temperature steam environment is solved, and the corrosion resistance of the coating is significantly improved.
Patent Information
- Application Number
- CN202411887670.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-04
AI Technical Summary
The existing chromium-permeable coating has poor stability in high-temperature steam environments and the oxide film is prone to peel off, which leads to intensified corrosion of boiler components and affects safety and economy.
By adding rare earth oxide La2O3 and modified element Hf to the permeate component and carrying out embedding and permeation treatment in a vacuum environment, the permeability, activation effect and oxidation and anti-peeling properties of the coating are improved.
The corrosion resistance of chrome-permeable coating in 650℃ coal ash/flue gas corrosion environment is significantly improved, with a corrosion rate of less than 0.1 mg/cm2, and its corrosion resistance is 22 to 66 times higher than that of the base material.
Smart Images

Figure CN119753567A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material surface alloying and coating preparation, and specifically relates to a modification method for improving the corrosion resistance of a chromized coating. Background Art
[0002] In the field of thermal power generation, the operating costs and material costs caused by oxidation, corrosion and other problems on the inner and outer walls of flow components have increased by more than 20%. The corrosion of flow components with large aspect ratios has become an industry common problem and technical pain point that restricts the safe production and operation of the entire energy equipment.
[0003] Studies have shown that Cr2O3 coatings have significant effects in solving the problems of component oxidation corrosion, wear, and high-temperature ablation; however, Cr2O3 has poor stability in steam above 600°C, and the loose oxide film caused by volatile products will cause the oxide film to peel off, and further lead to pipe blockage and pipe burst accidents. In addition, the Cr content in the alloy matrix is relatively low. With the increase of service time, when the Cr content required for the growth of the oxide film is not replenished, the corrosion resistance of the alloy will also drop sharply. Therefore, it is of great practical significance to study and develop high-performance corrosion-resistant coatings and their preparation processes suitable for the inner and outer wall surfaces of pipelines for boiler units. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a modification method for improving the corrosion resistance of chromized coatings.
[0007] In order to solve the above technical problems, the present invention provides the following technical solution: a modification method for improving the corrosion resistance of chromized coating, characterized in that: comprising:
[0008] Clean, grind and pickle the surface of the workpiece to be infiltrated, and then clean it with deionized water and alcohol and dry it for later use;
[0009] Weigh and prepare the components of the solid phase infiltration agent according to the proportion, and prepare the solid phase infiltration agents of different proportions after ball milling for use;
[0010] The workpiece to be infiltrated and the infiltrant are placed in an embedding infiltration tank, placed in a vacuum heating furnace for high-temperature heat treatment, and after the insulation is completed, cooled to room temperature and taken out.
[0011] As a preferred embodiment of the modification method of the present invention, the surface pretreatment process of the workpiece is performed by washing with a high-pressure water gun or a high-pressure air flow for 5 to 15 minutes. After the cleaning is completed, the surface of the workpiece is polished with metallographic sandpaper to a roughness Ra of less than 0.8 μm, and then the surface of the workpiece is cleaned with hydrochloric acid and hydrofluoric acid with a mass concentration of 0.5% for 10 to 30 seconds. After completion, the workpiece surface is rinsed with deionized water and alcohol in turn and dried to provide a neat and metallic surface for subsequent embedding and infiltration.
[0012] As a preferred embodiment of the modification method of the present invention, the infiltration source is Cr powder, the modifier is Hf, the filler is SiC, the activator is NH4Cl, and the catalyst is La2O3.
[0013] As a preferred scheme of the modification method described in the present invention, the solid phase components are weighed by mass percentage, including 30-50% Cr, 2-7% Hf, 40-60% SiC, 1-5% NH4Cl and 2-7% La2O3, wherein the Cr powder is sieved through a 1000 mesh sieve, and the solid phase components are mixed by ball milling in a planetary ball mill, the ball milling speed is 350-400 rpm, and the time is 12-24 hours.
[0014] As a preferred solution of the modification method of the present invention, the workpiece to be infiltrated and the penetrant are placed together in the embedding infiltration groove, the workpiece to be infiltrated is placed in the middle of the penetrant powder, and the distance between adjacent workpieces is not less than 10 cm.
[0015] As a preferred embodiment of the modification method of the present invention, the high temperature heat treatment temperature is 1000-1150° C., and the insulation time is 1-5 hours.
[0016] Another object of the present invention is to overcome the deficiencies in the prior art and produce a chromized coating.
[0017] As a preferred embodiment of the preparation method of the present invention, the preheating treatment is medium frequency preheating at 220°C for 30 to 60 minutes.
[0018] As a preferred embodiment of the preparation method of the present invention, the coating slurry is sprayed onto the surface of the workpiece, wherein the spraying pressure is 0.5-2MPa, the coating layer thickness is 0.1-5mm, and the coating coverage is not less than 98%.
[0019] As a preferred embodiment of the chromized coating of the present invention, the chromized coating has a uniform and dense structure, a thickness of 6 to 42 μm, an average Cr atomic content of 19 to 31%, and a corrosion rate of less than 0.1 mg / cm in a 650°C coal ash / smoke corrosion environment. 2The corrosion resistance is 22 to 66 times higher than that of the parent material.
[0020] Beneficial effects of the present invention:
[0021] 1. The present invention adds rare earth oxide La2O3 to the infiltration agent component, which has the effect of promoting infiltration and activation, thereby improving the infiltration rate and coating quality. The addition of rare earth oxide can pin the grain boundary, strengthen the matrix structure, improve the surface hardness, and improve the bonding strength between the coating and the base material in the form of second phase precipitation on the basis of promoting the diffusion of halide;
[0022] 2. The present invention adds the modified element Hf to the infiltrant component. The addition of the modified element Hf can aggregate at the oxide grain boundary and hinder the further oxidation of the parent material. Its oxidation product HfO2 can pin the oxide film and enhance the anti-stripping performance of the oxide, thereby improving the corrosion resistance, corrosion resistance and oxidation resistance of the coating;
[0023] 3. The present invention increases the content of halides in the atmosphere and reduces the influence of other residual gases on the diffusion layer by carrying out embedding diffusion in a vacuum environment;
[0024] 4. The infiltration agent components used in the present invention do not contain any toxic, harmful or polluting components, and the remaining infiltration agent powder after embedding can be recovered and reused multiple times. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0026] Figure 1 This is the cross-sectional morphology of the layer in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0029] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0030] The raw materials used in the present invention come from:
[0031] 99.95% Cr powder was purchased from Sinopharm Chemical Reagent Co., Ltd. with the specification of Alfa-013796; NH4Cl was purchased from Sinopharm Chemical Reagent Co., Ltd., 99.8% SiC powder was purchased from Sinopharm Chemical Reagent Co., Ltd. with the specification of Alfa~014165; 99.6% Hf powder was purchased from Sinopharm Chemical Reagent Co., Ltd. with the specification of Alfa-010201; La2O3 was purchased from Sinopharm Chemical Reagent Co., Ltd. with the specification of Acros-C19329.
[0032] Instruments used in the embodiments of the present invention: vertical planetary ball mill purchased from Changsha Miqi Instrument Equipment Co., Ltd., model is YXQM-2L, and tubular furnace purchased from Tianjin Bona Thermoelectric Furnace Co., Ltd., model is BR-12NT-100 / 450.
[0033] Smoke corrosion test:
[0034] Grind the prepared fly ash fully and add appropriate amount of acetone to make a suspension. Use a brush to apply it evenly on the surface of the coating sample. The coating amount is about 50mg / cm 2 The sample was placed in a constant temperature tubular heating furnace and heated to 650°C. Mixed flue gas was continuously introduced into the tubular furnace at a flue gas flow rate of 100 mL / min. A honeycomb Pt mesh was used as a catalyst to convert SO2 into SO3. A saturated NaOH solution was used to neutralize the remaining SO2 in the tail gas at the outlet of the tubular furnace. After the corrosion test, the sample was taken out, the coal ash remaining on the surface of the sample was removed, and the sample was weighed after cleaning and drying.
[0035] Microhardness test: The hardness of the coating was measured using a HV-1000A microhardness tester. The test load was selected as 200g, the holding time was 10s, and 6 points at different horizontal positions were selected for testing. The average value was taken as the microhardness value of the coating. Bonding strength test: The coating surface of the sample was bonded to the mating part with an epoxy resin adhesive. During the bonding process, the axis of the coating sample and the mating part were kept coincident. The bonded sample was placed in a 120°C drying oven for curing for 2 hours. The test was performed on an Instron 3382 electronic bonding strength tester at a tensile speed of 0.1mm / min. The maximum tensile stress when the bonded sample broke was taken as the bonding strength between the prepared chromized coating and the substrate.
[0036] Example 1
[0037] Step 1. Take out the workpiece to be plated, use high-pressure air flow to rinse for 15 minutes to remove oil stains, dust, etc. on the surface of the workpiece and remove the oxide scale. After cleaning, use metallographic sandpaper to grind the surface of the workpiece to a roughness Ra less than 0.8μm, and then use 0.5% hydrochloric acid and hydrofluoric acid to clean the surface of the workpiece for 30s. After completion, rinse it with deionized water and alcohol in turn and dry it.
[0038] Step 2: Weigh the solid phase components according to mass ratio, including 40% Cr, 5% Hf, 45% SiC, 5% NH4Cl and 5% La2O3, place them in a planetary ball mill at 400 rpm for 24 hours to obtain a solid phase infiltration agent.
[0039] Step 3: Place the workpiece to be infiltrated and the infiltrant in the embedding infiltration tank, with the workpiece to be infiltrated placed in the middle of the infiltrant powder, with the distance between adjacent workpieces not less than 10 cm; -3 )Pa~(9×10 -3 )Pa vacuum degree, the heat treatment temperature is 1050℃, the insulation time is 4h, and then it is cooled to room temperature.
[0040] Example 2
[0041] Step 1. Take out the workpiece to be plated, use high-pressure air flow to rinse for 15 minutes to remove oil stains, dust, etc. on the surface of the workpiece and remove the oxide scale. After cleaning, use metallographic sandpaper to grind the surface of the workpiece to a roughness Ra less than 0.8μm, and then use 0.5% hydrochloric acid and hydrofluoric acid to clean the surface of the workpiece for 30s. After completion, rinse it with deionized water and alcohol in turn and dry it.
[0042] Step 2: Weigh the solid phase components according to the mass ratio, including 50% Cr, 2% Hf, 40% SiC, 5% NH4Cl and 3% La2O3, place them in a planetary ball mill at 400 rpm for 24 hours to obtain a solid phase infiltration agent.
[0043] Step 3: Place the workpiece to be infiltrated and the infiltrant in the embedding infiltration tank, with the workpiece to be infiltrated placed in the middle of the infiltrant powder, with the distance between adjacent workpieces not less than 10 cm; -3 )Pa~(9×10 -3 )Pa vacuum degree, the heat treatment temperature is 1000℃, the insulation time is 4h, and then it is cooled to room temperature.
[0044] Example 3
[0045] Step 1. Take out the workpiece to be plated, use high-pressure air flow to rinse for 15 minutes to remove oil stains, dust, etc. on the surface of the workpiece and remove the oxide scale. After cleaning, use metallographic sandpaper to grind the surface of the workpiece to a roughness Ra less than 0.8μm, and then use 0.5% hydrochloric acid and hydrofluoric acid to clean the surface of the workpiece for 30s. After completion, rinse it with deionized water and alcohol in turn and dry it.
[0046] Step 2: Weigh the solid phase components according to the mass ratio, including 40% Cr, 3% Hf, 50% SiC, 5% NH4Cl and 2% La2O3, place them in a planetary ball mill at 400 rpm for 24 hours to obtain a solid phase infiltration agent.
[0047] Step 3: Place the workpiece to be infiltrated and the infiltrant in the embedding infiltration tank, with the workpiece to be infiltrated placed in the middle of the infiltrant powder, with the distance between adjacent workpieces not less than 10 cm; -3 )Pa~(9×10 -3 )Pa vacuum degree, the heat treatment temperature is 1000℃, the insulation time is 4h, and then it is cooled to room temperature.
[0048] Example 4
[0049] Step 1. Take out the workpiece to be plated, use high-pressure air flow to rinse for 15 minutes to remove oil stains, dust, etc. on the surface of the workpiece and remove the oxide scale. After cleaning, use metallographic sandpaper to grind the surface of the workpiece to a roughness Ra less than 0.8μm, and then use 0.5% hydrochloric acid and hydrofluoric acid to clean the surface of the workpiece for 30s. After completion, rinse it with deionized water and alcohol in turn and dry it.
[0050] Step 2: Weigh the solid phase components according to mass ratio, including 50% Cr, 2% Hf, 45% SiC, 1% NH4Cl and 2% La2O3, place them in a planetary ball mill at 350 rpm for 20 hours to obtain a solid phase infiltration agent.
[0051] Step 3: Place the workpiece to be infiltrated and the infiltrant in the embedding infiltration tank, with the workpiece to be infiltrated placed in the middle of the infiltrant powder, with the distance between adjacent workpieces not less than 10 cm; -3 )Pa~(9×10 -3 )Pa vacuum degree, the heat treatment temperature is 1000℃, the insulation time is 4h, and then it is cooled to room temperature.
[0052] Example 5
[0053] Step 1. Take out the workpiece to be plated, use high-pressure air flow to rinse for 15 minutes to remove oil stains, dust, etc. on the surface of the workpiece and remove the oxide scale. After cleaning, use metallographic sandpaper to grind the surface of the workpiece to a roughness Ra less than 0.8μm, and then use 0.5% hydrochloric acid and hydrofluoric acid to clean the surface of the workpiece for 30s. After completion, rinse it with deionized water and alcohol in turn and dry it.
[0054] Step 2: Weigh the solid phase components according to the mass ratio, including 30% Cr, 7% Hf, 41% SiC, 5% NH4Cl and 7% La2O3, and place them in a planetary ball mill at 400rpm for 24h to obtain a solid phase infiltrant. Place the workpiece under Ar for laser cladding, with a laser power of 2KW, a scanning rate of 40mm / s, a spot diameter of 3mm, a workpiece rotation speed of 5r / min, and an Ar gas flow of 15L / min; after completion, cool to room temperature and rinse the surface residue of the workpiece with high-pressure airflow.
[0055] Step 3: Place the workpiece to be infiltrated and the infiltrant in the embedding infiltration tank, with the workpiece to be infiltrated placed in the middle of the infiltrant powder, with the distance between adjacent workpieces not less than 10 cm; -3 )Pa~(9×10 -3 )Pa vacuum degree, the heat treatment temperature is 1000℃, the insulation time is 4h, and then it is cooled to room temperature.
[0056] Example 6
[0057] Step 1. Take out the workpiece to be plated, use high-pressure air flow to rinse for 5 minutes to remove oil stains, dust, etc. on the surface of the workpiece and remove the oxide scale. After cleaning, use metallographic sandpaper to grind the surface of the workpiece to a roughness Ra less than 0.8μm, and then use 0.5% hydrochloric acid and hydrofluoric acid to clean the surface of the workpiece for 30s. After completion, rinse it with deionized water and alcohol in turn and dry it.
[0058] Step 2: Weigh the solid phase components according to the mass ratio, including 42% Cr, 3% Hf, 43% SiC, 5% NH4Cl and 7% La2O3, place them in a planetary ball mill at 400 rpm for 24 hours to obtain a solid phase infiltration agent.
[0059] Step 3: Place the workpiece to be infiltrated and the infiltrant in the embedding infiltration tank, with the workpiece to be infiltrated placed in the middle of the infiltrant powder, with the distance between adjacent workpieces not less than 10 cm; -3 )Pa~(9×10 -3 )Pa vacuum degree, the heat treatment temperature is 1100℃, the insulation time is 5h, and then it is cooled to room temperature.
[0060] Example 7
[0061] Step 1. Take out the workpiece to be plated, rinse it with a high-pressure water gun for 10 minutes to remove oil stains, dust, etc. on the surface of the workpiece and remove the oxide scale. After cleaning, use metallographic sandpaper to grind the surface of the workpiece to a roughness Ra less than 0.8μm, and then use 0.5% hydrochloric acid and hydrofluoric acid to clean the surface of the workpiece for 30s. After completion, rinse it with deionized water and alcohol in turn and dry it.
[0062] Step 2: Weigh the solid phase components according to the mass ratio, including 40% Cr, 7% Hf, 45% SiC, 3% NH4Cl and 5% La2O3, place them in a planetary ball mill at 400 rpm for 18 hours to obtain a solid phase infiltration agent.
[0063] Step 3: Place the workpiece to be infiltrated and the infiltrant in the embedding infiltration tank, with the workpiece to be infiltrated placed in the middle of the infiltrant powder, with the distance between adjacent workpieces not less than 10 cm; -3 )Pa~(9×10 -3 )Pa vacuum degree, the heat treatment temperature is 1150℃, the insulation time is 2h, and then it is cooled to room temperature.
[0064] Example 8
[0065] Step 1. Take out the workpiece to be plated, use high-pressure air flow to rinse for 15 minutes to remove oil stains, dust, etc. on the surface of the workpiece and remove the oxide scale. After cleaning, use metallographic sandpaper to grind the surface of the workpiece to a roughness Ra less than 0.8μm, and then use 0.5% hydrochloric acid and hydrofluoric acid to clean the surface of the workpiece for 30s. After completion, rinse it with deionized water and alcohol in turn and dry it.
[0066] Step 2: Weigh the solid phase components according to the mass ratio, including 32% Cr, 3% Hf, 58% SiC, 4% NH4Cl and 4% La2O3, place them in a planetary ball mill at 400 rpm for 24 hours to obtain a solid phase infiltration agent.
[0067] Step 3: Place the workpiece to be infiltrated and the infiltrant in the embedding infiltration tank, with the workpiece to be infiltrated placed in the middle of the infiltrant powder, with the distance between adjacent workpieces not less than 10 cm; -3 )Pa~(9×10 -3 )Pa vacuum degree, the heat treatment temperature is 1150℃, the insulation time is 4h, and then it is cooled to room temperature.
[0068] Example 9
[0069] Step 1. Take out the workpiece to be plated, use high-pressure air flow to rinse for 15 minutes to remove oil stains, dust, etc. on the surface of the workpiece and remove the oxide scale. After cleaning, use metallographic sandpaper to grind the surface of the workpiece to a roughness Ra less than 0.8μm, and then use 0.5% hydrochloric acid and hydrofluoric acid to clean the surface of the workpiece for 30s. After completion, rinse it with deionized water and alcohol in turn and dry it.
[0070] Step 2: Weigh the solid phase components according to the mass ratio, including 44% Cr, 4% Hf, 41% SiC, 4% NH4Cl and 7% La2O3, place them in a planetary ball mill at 350 rpm for 24 hours to obtain a solid phase infiltration agent.
[0071] Step 3: Place the workpiece to be infiltrated and the infiltrant in the embedding infiltration tank, with the workpiece to be infiltrated placed in the middle of the infiltrant powder, with the distance between adjacent workpieces not less than 10 cm; -3 )Pa~(9×10 -3 )Pa vacuum degree, the heat treatment temperature is 1050℃, the insulation time is 5h, and then it is cooled to room temperature.
[0072] Example 10
[0073] Step 1. Take out the workpiece to be plated, use high-pressure air flow to rinse for 15 minutes to remove oil stains, dust, etc. on the surface of the workpiece and remove the oxide scale. After cleaning, use metallographic sandpaper to grind the surface of the workpiece to a roughness Ra less than 0.8μm, and then use 0.5% hydrochloric acid and hydrofluoric acid to clean the surface of the workpiece for 10s. After completion, rinse with deionized water and alcohol in turn and dry.
[0074] Step 2: Weigh the solid phase components according to mass ratio, including 45% Cr, 6% Hf, 45% SiC, 1% NH4Cl and 3% La2O3, place them in a planetary ball mill at 350 rpm for 24 hours to obtain a solid phase infiltration agent.
[0075] Step 3: Place the workpiece to be infiltrated and the infiltrant in the embedding infiltration tank, with the workpiece to be infiltrated placed in the middle of the infiltrant powder, with the distance between adjacent workpieces not less than 10 cm; -3 )Pa~(9×10 -3 )Pa vacuum degree, the heat treatment temperature is 1150℃, the insulation time is 4h, and then it is cooled to room temperature.
[0076] The corrosion resistance of the chromized coatings prepared in Examples 1 to 10 in 650°C coal ash / smoke was tested. The mass change (mg / cm 2 ) as shown in Table 1.
[0077] Table 1
[0078]
[0079] It can be seen that the weight gain trend of the chromized coatings prepared in Examples 2, 3, 6 and 7 within 500 h conforms to the linear law, and the corrosion rate of the coatings in the 650°C coal ash / smoke environment is basically stable; the corrosion rate of the chromized coatings prepared in Examples 4, 5, 8 and 10 gradually accelerates after the corrosion time exceeds 200 h, and the corrosion rates are 0.00952 mg / (cm 2 ·h)、0.00940mg / (cm 2 ·h)、0.00830mg / (cm 2 ·h) and 0.00985mg / (cm 2 ·h); The weight gain trend of the coatings prepared in Examples 1 and 9 conforms to the parabolic law. The coatings have good corrosion resistance in a 650°C coal ash / smoke environment, and the average corrosion rates within 500h are 0.00664mg / (cm 2 ·h) and 0.000752mg / (cm 2 h).
[0080] In summary, the corrosion rates of the chromized coatings prepared in Examples 1 to 10 in 650°C coal ash / smoke are all less than 0.01 mg / (cm 2 h), reaching the complete anti-oxidation level, wherein the typical coating cross-sectional morphology of the coating prepared in Example 1 is as follows Figure 1 As shown in the figure, the coating has the lowest corrosion rate in 650℃ coal ash / flue gas, and has excellent corrosion resistance.
[0081] Comparative Example 1
[0082] The difference between this comparative example and Example 1 is that the solid phase components are replaced by: 40% Cr, 5% Re, 45% SiC, 5% NH4Cl and 5% La2O3.
[0083] Comparative Example 2
[0084] The difference between this comparative example and Example 1 is that the solid phase components are replaced by: 40% Cr, 5% Hf, 45% Al2O3, 5% NH4Cl, and 5% La2O3.
[0085] Comparative Example 3
[0086] The difference between this comparative example and Example 1 is that the solid phase components are replaced by: 40% Cr, 5% Hf, 45% SiC, 5% Cr2O3·5H2O and 5% La2O3.
[0087] Comparative Example 4
[0088] The difference between this comparative example and Example 1 is that the solid phase components are replaced by: 40% Cr, 5% Hf, 45% SiC, 5% NH4Cl and 5% Y2O3.
[0089] Comparative Example 5
[0090] The difference between this comparative example and Example 1 is that the heat treatment process in step (3) is replaced by: -3 )Pa~(9×10 -3 )Pa vacuum degree, the heat treatment temperature is 1150℃, the insulation time is 2h, and then it is cooled to room temperature.
[0091] The corrosion resistance of the chromized coatings prepared in Example 1 and Comparative Examples 1 to 5 in 650°C coal ash / smoke was tested. The mass changes (mg / cm 2 ) as shown in Table 3.
[0092] Table 3
[0093]
[0094]
[0095] It can be seen that the corrosion rate of the chromized coating prepared in Comparative Example 1 gradually accelerated after the corrosion time exceeded 200 h, and its corrosion rate reached 0.0124 mg / (cm 2 ·h), the corrosion resistance of the coating deteriorates, indicating that compared with the addition of Re in the solid phase component, the addition of Hf improves the performance and reduces the corrosion rate of the prepared chromized coating in 650℃ coal ash / flue gas by more than 30%, thereby improving the corrosion resistance of the coating at high temperature; the oxidation weight gain trend of the chromized coating prepared in comparative example 2 within 500h conforms to the linear law, and the average corrosion rate of the coating in 650℃ coal ash / flue gas is 0.01534mg / (cm 2 ·h), which is much higher than the corrosion rate of the coating prepared in Example 1, indicating that the corrosion resistance of the chromized coating prepared by replacing SiC in the solid phase component with Al2O3 is reduced; in the 650℃ coal ash / flue gas environment, the coating prepared in Comparative Example 3 has poor stability of the oxide film after the corrosion time exceeds 300h, and begins to lose weight, and the oxide film peels off in large quantities, indicating that the addition of halide NH4Cl combined with the vacuum embedding process can effectively improve the corrosion resistance of the prepared chromized coating; the oxidation weight gain trend of the chromized coating prepared in Comparative Example 5 within 500h conforms to the linear law, and the average corrosion rate of the coating in 650℃ coal ash / flue gas is 0.00816mg / (cm 2·h), which is higher than the corrosion rate of the coating prepared in Example 1, indicating that the corrosion resistance of the chromized coating prepared after the heat treatment temperature is replaced with 1150°C and the holding time is replaced with 2h is reduced.
[0096] The microhardness and bonding strength of the chromized coatings prepared in Example 1 and Comparative Example 4 were tested respectively. The microhardness and interface tensile bonding strength of the coating prepared in Example 1 were 372 HV and 1372 HV, respectively. 0.2 and 39.2MPa, the microhardness and interfacial tensile strength of the coating prepared in Comparative Example 4 were 250HV 0.2 and 27.5MPa, indicating that the rare earth oxide La2O3 added to the solid phase component of the present invention can strengthen the matrix structure, improve the surface hardness, and enhance the bonding strength between the coating and the parent material. At the same time, the addition of Hf and La2O3 can reduce the corrosion rate of the prepared chromized coating in 650℃ coal ash / smoke by more than 30%, thereby further improving the corrosion resistance of the coating at high temperatures.
[0097] Through the above-mentioned processes and steps, a modification method for improving the corrosion resistance of a chromized coating of the present invention is provided. Under the conditions of adjusting main process parameters such as the content of the penetrant component, the content of the added modifying element and the heat treatment parameters, a chromium coating with good metallurgical bonding having a thickness of 6 to 42 μm and a Cr atomic content of 19% to 31% is prepared; the chromium coating obtained by the present invention has a corrosion resistance that is 22 to 66 times higher than that of the parent material in a 650°C flue gas corrosion environment, and a corrosion resistance that is 27 to 74 times higher than that of the parent material in a 750°C flue gas corrosion environment, which indicates that the chromium coating prepared by the method of the present invention effectively improves the heat corrosion resistance of the alloy parent material in a flue gas environment.
[0098] The modification method for improving the corrosion resistance of the chromized coating in the present invention is suitable for austenitic steel and high-temperature alloy parts used in large boilers, oil and gas field transportation pipelines and other workpieces with large aspect ratios and various complex shapes. It has strong practicality, high diffusion rate, excellent membrane-base bonding, and extremely good industrial mass production benefits.
[0099] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A modification method for improving the corrosion resistance of a chromized coating, characterized in that: include, Clean, grind and pickle the surface of the workpiece to be infiltrated, and then clean it with deionized water and alcohol and dry it for later use; Weigh and prepare the components of the solid phase infiltration agent including the infiltration source, the modifier, the filler, the activator and the infiltration catalyst in proportion, and prepare the solid phase infiltration agents in different proportions after ball milling for use; The workpiece to be infiltrated and the infiltrant are placed in an embedding infiltration tank, placed in a vacuum heating furnace for high-temperature heat treatment, and after the insulation is completed, cooled to room temperature and taken out.
2. A modification method for improving the corrosion resistance of chromized coating according to claim 1, characterized in that: The workpiece surface pretreatment process comprises the following steps: cleaning with a high-pressure water gun or high-pressure air flow for 5 to 15 minutes; after cleaning, the workpiece surface is polished with metallographic sandpaper to a roughness Ra of less than 0.8 μm; then, the workpiece surface is cleaned with hydrochloric acid and hydrofluoric acid with a mass concentration of 0.5% for 10 to 30 seconds; after completion, the workpiece surface is rinsed with deionized water and alcohol in turn and dried to provide a clean surface with a metallic luster for subsequent embedding and infiltration.
3. A modification method for improving the corrosion resistance of chromized coating according to claim 1, characterized in that: The infiltration source is Cr powder, the modifier is Hf, the filler is SiC, the activator is NH4Cl, and the infiltration catalyst is La2O3.
4. A modification method for improving the corrosion resistance of chromized coating according to claim 1, characterized in that: The solid phase components are weighed by mass percentage, including 30-50% Cr, 2-7% Hf, 40-60% SiC, 1-5% NH4Cl and 2-7% La2O3, wherein the Cr powder is sieved through a 1000-mesh sieve, and the solid phase components are mixed by ball milling in a planetary ball mill, the ball milling speed is 350-400 rpm, and the time is 12-24 hours.
5. A modification method for improving the corrosion resistance of chromized coating according to claim 1, characterized in that: The workpiece to be infiltrated and the infiltrant are placed together in the embedding infiltration groove, the workpiece to be infiltrated is placed in the middle of the infiltrant powder, and the distance between adjacent workpieces is not less than 10 cm.
6. A modification method for improving the corrosion resistance of chromized coating according to claim 1, characterized in that: The high temperature heat treatment temperature is 1000-1150° C., and the insulation time is 1-5 hours.
7. The chromized coating obtained by the modification method according to any one of claims 1 to 6.
8. The chromized coating according to claim 7, characterized in that: The chromized coating has a uniform and dense structure, a thickness of 6 to 42 μm, and an average Cr atomic content of 19 to 31%. The corrosion rate in a 650°C coal ash / smoke corrosion environment is less than 0.1 mg / cm 2 The corrosion resistance is 22 to 66 times higher than that of the parent material.